New rationales for taxing the digital economy: lessons from the OECD Pillar One consultations - Listokin, Siona (Frontiers in Political Science, 2025)
IntroductionThe taxation of multinational digital firms presents unique challenges due to the decoupling of value creation from physical presence. While international bodies like the OECD have advanced policy proposals—most notably through Pillar One—there remains a broader conceptual debate on how digitalization reshapes traditional tax norms. This study seeks to document and categorize emerging, arguments for reforming global tax rules in response to digital economic activity.MethodsThe study analyzes all stakeholder submissions to the OECD’s Pillar One consultation process. A qualitative coding approach was used to identify recurring themes and conceptual justifications for reforming the allocation of taxing rights.ResultsThe analysis identified several categories of nontraditional arguments for revising international tax norms. These include proposals to shift taxing rights away from residence-based physical presence rules; arguments to internalize the societal costs of digital marketplaces; and the use of taxation as a regulatory mechanism to constrain digital platform dominance. These conceptual innovations go beyond traditional efficiency or fairness arguments in tax policy.DiscussionWhile not always reflected in final OECD policy outcomes, these arguments provide a taxonomy of emerging ideas that could influence future tax debates—particularly as generative AI and digital platforms increasingly dissociate economic activity from territorial nexus.